Factors influencing timely diagnosis in neurolymphomatosis - Doubrovinskaia, Sofia; Egert, Antonia; Karschnia, Philipp; Scheffler, Georg T.; Traub, Benjamin-Leon; Galluzzo, Daniela; Huttner, Anita; Fulbright, Robert K.; Baehring, Joachim M.; Kaulen, Leon D. (Journal of neuro-oncology, 2024)
Neurolymphomatosis refers to infiltration of the peripheral nervous system (PNS) by non-Hodgkin lymphoma (NHL). Diagnostic intervals in neurolymphomatosis and factors delaying diagnosis have not been evaluated. We therefore aimed to analyze diagnostic intervals in a large cohort.
Online veröffentlicht: 8. August 2025
Gesehen am 08.05.2025